Chain Decisions in Digital Government: Between Validity, Integration, and Legal Consequences - Firzhal Arzhi Jiwantara; Rudy Herlambang; Abd Rahman; Muhamad Husni (IHSA Institute, 2026)
The development of digital government in Indonesia presents a new paradigm in administrative decision-making through integrated electronic systems. Decisions in digital government often have a cascading nature, where initial decisions form the basis for subsequent decisions. This study analyzes the validity of cascading decisions and the legal consequences of digital system integration, focusing on how flaws at one stage can affect the validity of subsequent decisions, and how system synchronization determines the legal consequences of data or procedural inconsistencies. The research methods used are literature review and normative analysis of national regulations, including Presidential Regulation No. 95 of 2018 concerning Electronic Systems and Transactions (SPBE) and Government Regulation No. 82 of 2012 concerning the Implementation of Electronic Systems and Transactions. The results show that the validity of cascading decisions is highly dependent on compliance with legal procedures, data integrity, and the application of administrative law principles. Meanwhile, good digital system integration can ensure consistency, legal certainty, and accountability, while integration failures have the potential to create legal uncertainty and administrative disputes. This study emphasizes that digital government is not merely a technological transformation, but also a legal transformation that requires strict system and procedural management.